2013
DOI: 10.1038/aja.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical outcomes after robot-assisted radical prostatectomy in patients with follow-up more than 5-years

Abstract: In this study, we assessed biochemical outcomes after robot-assisted radical prostatectomy (RARP). Between July 2005 and November 2007, one hundred and seventy-six consecutive patients treated by RARP without neoadjuvant treatment were included in this study. All procedures were performed by a single surgeon and the median follow-up period was 60 months (interquartile range (IQR): 59-69). The median prostate specific antigen was 7.50 ng ml 21 (IQR: 5.14-11.45) and 39.2% of the patients were classified as inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Kim et al reported the Korean BCRFS rate after RARP, which seems to be in agreement with our rates. 24 They mentioned that their series included a higher proportion of high-grade disease and nonorgan-confined tumors compared with those in other RARP series, and a significant proportion of high-grade disease was also noted in studies of Chinese and Japanese populations. In addition, other Japanese BCRFS rates including open or laparoscopic RP were lower than the rate in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…Kim et al reported the Korean BCRFS rate after RARP, which seems to be in agreement with our rates. 24 They mentioned that their series included a higher proportion of high-grade disease and nonorgan-confined tumors compared with those in other RARP series, and a significant proportion of high-grade disease was also noted in studies of Chinese and Japanese populations. In addition, other Japanese BCRFS rates including open or laparoscopic RP were lower than the rate in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…Our group was the first to report on BCR after RARP with a median follow up of 60 months; however, our previous studies had some limitations: a small number of patients (n = 176), the presence of LN metastases was not included in the analysis of BCR and we did not report on survival rates. 6 In the current study, we extended our analysis to present our entire updated experience with the largest reported RARP series among an Asian population (n = 800) and the longest follow-up period (median follow up of 64 months). We recorded the nodal status and its impact on BCR, as most of our patients (97.1%) underwent PLND.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike ORP, reports on long-term oncological follow up after RARP are insufficient. Just a few studies reported 5-year oncological outcomes after RARP, [3][4][5][6] with only one recent study having a 10-year follow-up period. 7 Previously, we reported BRC in a small cohort of patients (n = 176) who underwent RARP at our institution (Department of Urology and Urological Science Institute, Yonsei University College of Medicine, Seoul, Korea) between 2005 and 2007, and the BCRFS rates at 3 and 5 years were 85.6% and 81.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations